ENHANCING ORGANISATIONAL COMMITMENT THROUGH E-TRAINING CAPABILITY IN A PARAMILITARY ORGANISATION: THE STUDY OF NIGERIA IMMIGRATION SERVICE (ABUJA JOURNAL OF BUSINESS AND MANAGEMENT, 2025)
This study was carried out to examine the effect of e-training capability on organisational commitment in a paramilitary organisation. The study focused on the capability of e-training as enhanced by digital technology to achieve organisational commitment. The quantitative case-study research was carried out within the Nigeria Immigration Service headquarters in Abuja Nigeria, using survey questionnaire to source data. Random sampling technique was deplored from a population of 1772 senior personnel with a sample size of 326 respondents to assess their perception on the capability of e-training activities on organisational commitment. The data gathered was subjected to analysis in both descriptive statistics, using percentages and inferential statistics using regression analysis with the aid of Statistical Package for Social Science (SPSS) version 26. The findings revealed a positive significant relationship between e-training and organisational commitment with the model showing R2 as the variability in the dependent variable organisational commitment as explained by the independent variable, e-training. The R2 value .0242, indicates that 24.2 % of the change in the dependent variable, organisational commitment is explained by the independent variable, e-training. The F-statistics value is 90.317 with P-value of 0.000, which is statistically significant as it is less than 0.05. The implication of this is that e-training has the capability to enhance organisational commitment among the employees of the Nigeria Immigration Service. The Nigeria Immigration Service should maintain and build more on the digital technologies that enhances e-training to sustain the commitment level among the employees.